Innovation Of Praline With Kacang Kapri Daun Jeruk: A Balinese Distinctive Culinary Souvenir - Hansen Budi Gunawan; Ni Ketut Veri Kusumaningrum; Billy Tanius (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
This study aims to develop a praline innovation by utilizing “kacang kapri daun jeruk”, a distinctive Balinese culinary Souvenir, as a filling, and to evaluate consumer acceptance of the product. The research employed a research and development (R&D) method which included the stages of identifying potentials and problems, data collection, product planning, initial product development, product testing, product revision, field testing, and final product revision of pralines using three types of chocolate which are white chocolate, milk chocolate, and dark chocolate, which in this study were also compared to determine their suitability and level of consumer acceptance. A hedonic test was conducted involving five expert panelists and twenty-five general panelists, assessing color, aroma, texture, taste, and overall acceptability. The milk chocolate variant achieved the highest overall score and received positive responses from the panelists, while the dark chocolate variant obtained the lowest overall score. In conclusion, milk chocolate pralines filled with “kacang kapri daun jeruk”, a distinctive Balinese culinary souvenir, have the potential to become an innovative value-added gift that strengthens Bali’s culinary identity with further opportunities to improve product quality.